Efficiency of Industrially Relevant Atropisomeric Diphosphines in Copper-Catalyzed 1,4-Asymmetric Conjugate Addition of Dialkylzincs to Cyclic or Acyclic Enones or Dienones - Morin, Marie S. T.; Vives, Thomas; Baslé, Olivier; Crévisy, Christophe; Ratovelomanana-Vidal, Virginie; Mauduit, Marc (Synthesis, 2015)
Industrially relevant atropisomeric diphosphines such as 2,2′-bis(diphenylphosphino)-1,1′-binaphthyl (BINAP), 6,6′-bis(diphenylphosphino)-2,2′,3,3′-tetrahydro-5,5′-bi-1,4-benzodioxin (SYNPHOS), and 5,5′-bis(diphenylphosphino)-2,2,2′,2′-tetrafluoro-4,4′-bi-1,3-benzodioxole (DIFLUORPHOS) have demonstrated their efficiency in the copper-catalyzed asymmetric conjugate addition of various dialkylzincs to α-aryl enones, α-aryl dienones, and cyclic dienones. Excellent 1,4- or 1,6-regioselectivities and enantioselectivities (up to 97% ee) were attained, even with challenging sterically hindered Michael acceptors.
Keywords: enones; addition reactions; asymmetric catalysis; copper; phosphines; dialkylzinc reagents